Nice Angles, But Not-So-Nice Answer

Geometry Level 5

Four points A , B , C , D A,B,C,D satisfy A B = 1 AB=1 , B C = 2 BC=2 , C D = 3 CD=3 , A B C = 4 5 \angle ABC=45^{\circ} , and B C D = 6 0 \angle BCD=60^{\circ} . The largest possible value of A D AD can be expressed in the form a + b c \sqrt{a+\sqrt{b-\sqrt{c}}} for positive integers a , b , c a,b,c . Find a + b + c a+b+c .


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Isaac Lu
Mar 26, 2014

'

Draw the quadrilateral ABCD.

m A B C = 4 5 and m B C D = 6 0 m\angle ABC=45^\circ\text{ and }m\angle BCD=60^\circ

From point A \bf{A} , draw a line perpendicular to B C \overline{BC} at point E \bf{E} .

From point D \bf{D} , draw a line perpendicular to B C \overline{BC} at point F \bf{F} .

From point A \bf{A} , draw a line perpendicular to D F \overline{DF} (and parallel to B C \overline{BC} ) at point G \bf{G} .

The triangles Δ A B E and Δ D F C are special triangles. \text{The triangles }\Delta ABE\text{ and }\Delta DFC\text{ are special triangles.}

That means A E = B E = 2 2 \boxed{AE=BE=\displaystyle\frac{\sqrt{2}}{2}} .

F C = C D cos 6 0 0 F C = 3 2 FC=CD\cos{60^0}\rightarrow\boxed{FC=\displaystyle\frac{3}{2}}

D F = C D sin 6 0 0 D F = 3 2 3 DF=CD\sin{60^0}\rightarrow\boxed{DF=\displaystyle\frac{3}{2}\sqrt{3}}

B C = B E + E F + F C BC=BE+EF+FC and B C = 2 BC=2

2 = 2 2 + E F + 3 2 2=\displaystyle\frac{\sqrt{2}}{2}+\color{#0000ff}{EF}+\frac{3}{2}

E F = 1 2 2 \boxed{EF=\displaystyle\frac{1-\sqrt{2}}{2}}

A G F E is a rectangle. Therefore, A G is parallel and equal to E F and A E is parallel and equal to G F AGFE\text{ is a rectangle. Therefore, }AG\text{ is parallel and equal to }EF\text{ and }AE\text{ is parallel and equal to }GF

A E = G F = 2 2 and E F = A G = 1 2 2 AE=\boxed{GF=\displaystyle\frac{\sqrt{2}}{2}}\text{ and }EF=\boxed{AG=\displaystyle\frac{1-\sqrt{2}}{2}}

D F = D G + G F DF=DG+GF

3 2 3 = D G + 2 2 \displaystyle\frac{3}{2}\sqrt{3}=DG+\displaystyle\frac{\sqrt{2}}{2}

D G = 3 3 2 2 DG=\displaystyle\frac{3\sqrt{3}-\sqrt{2}}{2}

Consider the triangle Δ A G D \Delta AGD . A D AD can be measured using the P y t h a g o r e a n T h e o r e m \bf{Pythagorean Theorem} .

A D = A G 2 + D G 2 AD=\sqrt{AG^2+DG^2}

A D = ( 1 2 2 ) 2 + ( 3 3 2 2 ) 2 AD=\sqrt{\left(\displaystyle\frac{1-\sqrt{2}}{2}\right)^2+\left(\displaystyle\frac{3\sqrt{3}-\sqrt{2}}{2}\right)^2}

A D = 8 1 2 2 + 3 2 6 AD=\sqrt{8-\displaystyle\frac{1}{2}\sqrt{2}+\displaystyle\frac{3}{2}\sqrt{6}}

It is said in the problem that AD can be written in the form a + b c \text{It is said in the problem that AD can be written in the form }\sqrt{a+\sqrt{b-\sqrt{c}}}

a + b c = 8 1 2 2 + 3 2 6 \sqrt{a+\sqrt{b-\sqrt{c}}}=\sqrt{8-\displaystyle\frac{1}{2}\sqrt{2}+\displaystyle\frac{3}{2}\sqrt{6}}

Square both sides of the equation to get \text{Square both sides of the equation to get }

a + b c = 8 + 3 2 6 1 2 2 \color{#ff0000}{a}+\sqrt{b-\sqrt{c}}=\color{#ff0000}{8}+\displaystyle\frac{3}{2}\sqrt{6}-\displaystyle\frac{1}{2}\sqrt{2}

We can now conclude that a = 8 \boxed{a=8}

Since a = 8 a=8 , we cancel it to get the new equation b c = 3 2 6 1 2 2 \sqrt{b-\sqrt{c}}=\displaystyle\frac{3}{2}\sqrt{6}-\displaystyle\frac{1}{2}\sqrt{2}

Square both sides.

( b c ) 2 = ( 3 2 6 1 2 2 ) 2 (\sqrt{b-\sqrt{c}})^2=\left(\displaystyle\frac{3}{2}\sqrt{6}-\displaystyle\frac{1}{2}\sqrt{2}\right)^2

b c = 14 3 3 \color{#ff0000}{b}-\sqrt{c}=\color{#ff0000}{14}-3\sqrt{3}

We conclude that b = 14 \boxed{b=14} .

That leaves us c = 3 3 \sqrt{c}=3\sqrt{3} or c = 27 \sqrt{\color{#ff0000}{c}}=\sqrt{\color{#ff0000}{27}} .

Therefore, c = 27 \boxed{c=27}

a + b + c = 8 + 14 + 27 = 49 a+b+c=8+14+27=\boxed{49}

Very nice(y) two thumbs up!!

Reynan Henry - 7 years, 2 months ago

Definitely a very well-written solution! Kudos for explaining it clearer than I can ever do! Deserves more than just an upvote from me.

Daniel Liu - 7 years, 2 months ago

Exactly what I did! Even the squaring part! Nicely written out solution man.

Xuming Liang - 7 years, 2 months ago

Log in to reply

Hey, I'd just like to congratulate you on being the first person to finish my Best of Me set!

Daniel Liu - 7 years, 2 months ago

In this solution, EF = (1-sqrt(2))/2, which is less than 0. However, the answer comes out right. Why does this work? (Besides that, very nice solution :D)

Alec Zhang - 7 years, 1 month ago

Log in to reply

You can think of it like going into the negative direction on the number line. The absolute distance is always positive, but the value of the distance is negative. Did that make any sense?

Daniel Liu - 7 years, 1 month ago

Log in to reply

wait so are you saying we can flip the negative value of EF in the opposite direction to become a positive value? in that case, then instead of the points being in the order BEFC, it's actually BFEC--the two triangles overlap? (!)

Alec Zhang - 7 years, 1 month ago
Daniel Liu
Mar 16, 2014

Let us put this problem on the complex plane. Let C C be the origin, and let B = 2 B=-2 .

Clearly, D = 3 cis ( 24 0 ) D=3\text{cis}(240^{\circ}) and A = cis ( 4 5 ) 2 A=\text{cis}(45^{\circ})-2 for A D AD to be maximum.

All we need to do now is to compute A D = ( 3 cis ( 24 0 ) ) ( cis ( 4 5 ) 2 ) AD=\left|(3\text{cis}(240^{\circ}))-(\text{cis}(45^{\circ})-2)\right| .

Note that cis ( 24 0 ) = 1 2 i 3 2 \text{cis}(240^{\circ})=-\dfrac{1}{2}-\dfrac{i\sqrt{3}}{2} and cis ( 4 5 ) = 2 2 + i 2 2 \text{cis}(45^{\circ})=\dfrac{\sqrt{2}}{2}+\dfrac{i\sqrt{2}}{2} . Substituting these values in, we have A D = 3 ( 1 2 i 3 2 ) ( 2 2 + i 2 2 2 ) = ( 3 2 3 i 3 2 ) ( 2 2 + i 2 2 ) + 2 = 1 2 2 ( 3 3 + 2 2 ) i = ( 1 2 2 ) 2 + ( 3 3 + 2 2 ) 2 = 32 + 6 6 2 2 4 = 8 + 3 6 2 2 \begin{aligned}AD&=\left|3\left(-\dfrac{1}{2}-\dfrac{i\sqrt{3}}{2}\right)-\left(\dfrac{\sqrt{2}}{2}+\dfrac{i\sqrt{2}}{2}-2\right)\right|\\&=\left|\left(-\dfrac{3}{2}-\dfrac{3i\sqrt{3}}{2}\right)-\left(\dfrac{\sqrt{2}}{2}+\dfrac{i\sqrt{2}}{2}\right)+2\right|\\&=\left|\dfrac{1-\sqrt{2}}{2}-\left(\dfrac{3\sqrt{3}+\sqrt{2}}{2}\right)i\right|\\ &= \sqrt{\left(\dfrac{1-\sqrt{2}}{2}\right)^2+\left(\dfrac{3\sqrt{3}+\sqrt{2}}{2}\right)^2}\\ &= \sqrt{\dfrac{32+6\sqrt{6}-2\sqrt{2}}{4}} \\&= \sqrt{8+\dfrac{3\sqrt{6}-\sqrt{2}}{2}}\end{aligned}

However, this isn't the format that the problem asked for. How can we change it to it the format?

We conjecture that 3 6 2 2 = b c \dfrac{3\sqrt{6}-\sqrt{2}}{2}=\sqrt{b-\sqrt{c}} . We square 3 6 2 2 \dfrac{3\sqrt{6}-\sqrt{2}}{2} to get ( 3 6 2 2 ) 2 = 14 27 \left(\dfrac{3\sqrt{6}-\sqrt{2}}{2}\right)^2=14-\sqrt{27} . Now squarerooting again we arrive at the conclusion that 3 6 2 2 = 14 27 \dfrac{3\sqrt{6}-\sqrt{2}}{2}=\sqrt{14-\sqrt{27}} .

Therefore A D = 8 + 14 27 AD=\sqrt{8+\sqrt{14-\sqrt{27}}} and our desired answer if 8 + 14 + 27 = 49 8+14+27=\boxed{49} .

Holy pooping rabbits. That's wicked. :D

Finn Hulse - 7 years, 2 months ago

Yeah, or a real plane would also do. :) (cartesian)

Himanshu Arora - 7 years ago

First, we form a triangle with vertexes B B , C C and D D , so we can find B D \overline{BD} applying cosine's law: B D 2 = C D 2 + B C 2 2 ( C D ) ( B C ) ( c o s B C D ) \overline{BD}^{2}=\overline{CD}^2+\overline{BC}^2-2(\overline{CD})(\overline{BC})(cos \angle BCD)

B D 2 = ( 3 ) 2 + ( 2 ) 2 2 ( 3 ) ( 2 ) ( c o s 60 ° ) \overline{BD}^{2}=(3)^{2}+(2)^{2}-2(3)(2)(cos 60°)

B D 2 = 13 12 ( 1 2 ) \overline{BD}^{2}=13-12(\frac{1}{2})

B D 2 = 13 6 \overline{BD}^{2}=13-6

B D 2 = 7 \overline{BD}^{2}=7

B D = 7 \overline{BD}=\sqrt{7}

Now, we observe that A D B + C B D = A B C = 45 ° \angle ADB + \angle CBD = \angle ABC = 45° , so A B D = 45 ° C B D \angle ABD = 45° - \angle CBD , now we find the angle C B D \angle CBD , again, by cosine's law: c o s C B D = B D 2 + B C 2 C D 2 2 B D B C cos \angle CBD = \frac{\overline{BD}^{2}+\overline{BC}^{2}-\overline{CD}^2}{2\overline{BD}\overline{BC}}

c o s C B D = ( 7 ) 2 + ( 2 ) 2 ( 3 ) 2 2 ( 7 ) ( 2 ) cos \angle CBD = \frac{(\sqrt{7})^{2}+(2)^{2}-(3)^2}{2(\sqrt{7})(2)}

c o s C B D = 7 + 4 9 4 7 cos \angle CBD = \frac{7+4-9}{4\sqrt{7}}

c o s C B D = 2 4 7 cos \angle CBD = \frac{2}{4\sqrt{7}}

c o s C B D = 1 2 7 cos \angle CBD = \frac{1}{2\sqrt{7}}

Now, we find A B D \angle ABD , by applying cosine to both sides of: A B D = 45 ° C B D \angle ABD = 45° - \angle CBD : c o s ( A B D ) = c o s ( 45 ° C B D ) cos(\angle ABD) = cos(45° - \angle CBD)

c o s ( A B D ) = c o s ( 45 ° ) c o s ( C B D ) + s i n ( 45 ° ) s i n ( C B D ) cos(\angle ABD) = cos(45°)cos(\angle CBD) + sin(45°)sin(\angle CBD)

c o s ( A B D ) = 2 2 c o s ( C B D ) + 2 2 s i n ( C B D ) cos(\angle ABD) = \frac{\sqrt{2}}{2}cos(\angle CBD) + \frac{\sqrt{2}}{2}sin(\angle CBD)

c o s ( A B D ) = 2 2 ( c o s ( C B D ) + s i n ( C B D ) cos(\angle ABD) = \frac{\sqrt{2}}{2}(cos(\angle CBD) + sin(\angle CBD) )

See that we have c o s ( C B D ) cos(\angle CBD) , now we have to find s i n ( C B D ) sin(\angle CBD) : s i n ( C B D ) = 1 c o s ( C B D ) 2 sin(\angle CBD)=\sqrt{1-cos(\angle CBD)^{2}}

s i n ( C B D ) = 1 ( 1 2 7 ) 2 sin(\angle CBD)=\sqrt{1-(\frac{1}{2\sqrt{7}})^{2}}

s i n ( C B D ) = 1 1 28 sin(\angle CBD)=\sqrt{1-\frac{1}{28}}

s i n ( C B D ) = 28 1 28 sin(\angle CBD)=\sqrt{\frac{28-1}{28}}

s i n ( C B D ) = 27 28 sin(\angle CBD)=\sqrt{\frac{27}{28}}

s i n ( C B D ) = 3 3 2 7 sin(\angle CBD)=\frac{3\sqrt{3}}{2\sqrt{7}}

Replace these values to find c o s ( A B D ) cos(\angle ABD) :

c o s ( A B D ) = 2 2 ( 1 2 7 + 3 3 2 7 ) cos(\angle ABD) = \frac{\sqrt{2}}{2}(\frac{1}{2\sqrt{7}}+\frac{3\sqrt{3}}{2\sqrt{7}})

c o s ( A B D ) = 2 + 3 6 4 7 cos(\angle ABD) = \frac{\sqrt{2}+3\sqrt{6}}{4\sqrt{7}}

Finally, we form a triangle with vertexes A A , D D and B B , and we apply cosine's law to find A D \overline{AD} : A D 2 = A B 2 + B D 2 2 ( A B ) ( B D ) ( c o s ( A B D ) ) \overline{AD}^{2}=\overline{AB}^{2}+\overline{BD}^{2}-2(\overline{AB})(\overline{BD})(cos(\angle ABD))

A D 2 = ( 1 ) 2 + ( 7 ) 2 2 ( 1 ) ( 7 ) ( 2 + 3 6 4 7 \overline{AD}^{2}=(1)^{2}+(\sqrt{7})^{2}-2(1)(\sqrt{7})(\frac{\sqrt{2}+3\sqrt{6}}{4\sqrt{7}} )

A D 2 = 1 + 7 2 + 3 6 2 \overline{AD}^{2} = 1+7-\frac{\sqrt{2}+3\sqrt{6}}{2}

A D = 8 2 + 3 6 2 \overline{AD}=\sqrt{8-\frac{\sqrt{2}+3\sqrt{6}}{2}}

A D = 8 ( 2 + 3 6 2 ) 2 \overline{AD}=\sqrt{8-\sqrt{(\frac{\sqrt{2}+3\sqrt{6}}{2}})^{2}}

A D = 8 54 + 12 3 + 2 4 \overline{AD}=\sqrt{8-\sqrt{\frac{54+12\sqrt{3}+2}{4}}}

A D = 8 56 + 12 3 4 \overline{AD}=\sqrt{8-\sqrt{\frac{56+12\sqrt{3}}{4}}}

A D = 8 14 + 3 3 \overline{AD}=\sqrt{8-\sqrt{14+3\sqrt{3}}}

A D = 8 14 + 27 \overline{AD}=\sqrt{8-\sqrt{14+\sqrt{27}}}

Hence, a = 8 a=8 , b = 14 b=14 , and c = 27 c=27 . So, a + b + c = 49 a+b+c=\boxed{49}

Thanks for taking your time to write out that extremely long solution!

Daniel Liu - 7 years, 2 months ago

I get the length of AD to be 1.9022741. The lengths of each of the 3 (correct) answers differ from each other and from mine. How does one account for this?

Guiseppi Butel - 7 years ago

Log in to reply

Yes, I was wrong with a sign on the beginning and in the end.

Alan Enrique Ontiveros Salazar - 6 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...